Adult supratentorial primitive neuroectodermal tumour presenting as intracranial haemorrhage: Case report. (March 2017) - Black-Tiong, Sean P.; Sandler, Simon J.I.; Otto, Sophia; Wells, Adam J.
Highlights: Intracranial haemorrhage due to supratentorial primitive neuroectodermal tumour. Rare presentation of a rare tumour, literature is reviewed. Biopsy advised to exclude tumour in otherwise unexplained intracranial haemorrhage. Abstract: Primitive neuroectodermal tumours (PNET) are highly malignant tumours with an aggressive clinical behaviour. Commonly seen in children, they are uncommon in the adult population, and rare in the supratentorial location. Adult supratentorial PNETs (ST-PNET) typically present with symptoms relating to raised intracranial pressure, seizures, or focal neurological deficits. Presentation with intracranial haemorrhage has been reported only twice before in the literature, one of which was fatal. We report the case of intracranial haemorrhage secondary to ST-PNET in a young adult and her immediate management.